Adenosinergic Pathway and Linked Suppression: Two Critical Suppressive Mechanisms of Human Donor Antigen Specific Regulatory T Cell Lines Expanded Post Transplant - Tripathi, Sudipta; Martin-Moreno, Paloma L.; Kavalam, George; Schreiber, Brittany L.; Waaga-Gasser, Ana Maria; Chandraker, Anil (Frontiers in Immunology, 2022)
Regulatory T cells are an important component of an immune response shaping the overall behavior to potential antigens including alloantigens. Multiple mechanisms have been shown to contribute towards developing and sustaining a immunological regulatory response. One of the described contact dependent suppressive mechanisms regulatory cells have been shown to utilize is through the production of adenosine from extracellular ATP mediated by CD39 and CD73. In this study we demonstrate that the adenosinergic pathway plays a major role in the suppressive/regulatory effects antigen specific regulatory T cell enriched lines (ASTRLs) that have been of expanded ex vivo from stable kidney transplant patients. We have previously shown that these ASTRL cells are capable of suppressing alloimmune responses in vitro and significantly prolonging allograft survival in an animal model of kidney transplantation. For this study nineteen ASTRLs were expanded from 17 kidney transplant patients by repeated stimulation of recipient peripheral blood mononuclear cells with donor specific HLA-DR peptides. All 19 ASTRLs showed upregulation of numerous markers associated with regulatory cells and were able to inhibit donor antigen specific T cell proliferation in a dose dependent fashion. ASTRLs suppressed indirect and direct alloimmune responses compatible with our previous animal study findings. Upregulation of both CD39 and CD73 was observed post expansion and ASTRLs demonstrated extracellular hydrolysis of ATP, indicating functionality of the upregulated proteins. We also showed that inhibition of the adenosinergic pathway using inhibitors of CD39 resulted in abrogation of suppression and increased antigen specific T cell proliferation. This demonstrates that the main mechanism of action of the suppressive activity donor peptide driven ASTRLs generated from kidney transplant patients is the adenosinergic pathway. Furthermore this suggests the possibility that combining infusion of Tregs with other treatments, such as adenosine receptor agonists or increasing CD39 expression in the grafts may further enhance a regulatory response to the allograft and possibly achieve transplantation tolerance.